2002
DOI: 10.1068/b2779
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of the GIS—Fuzzy Set Approach in Evaluating the Urban Residential Environment

Abstract: The authors' focus was to determine the usefulness of the fuzzy set approach in evaluating the urban residential environment, compared with the crisp (or Boolean) approach. Particular emphasis was placed upon the comparison of evaluation results produced by the two methods within a geographic information system (GIS). This comparison highlighted the advantages of the GIS-fuzzy set approach as follows. First, it was revealed that the fuzzy set approach could reduce excessive abstraction or exaggeration in envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Since the people reflect their life styles and knowledge to the environment they live, the city quality reflects the life quality at the same time. In this context, the World Health Organization recommends including the following criterias for assessment of life quality: usage of the space, protection of historical, cultural and natural values, accessibility to services, planning, building design, urban design [12].…”
Section: Life Quality Descriptionsmentioning
confidence: 99%
“…Since the people reflect their life styles and knowledge to the environment they live, the city quality reflects the life quality at the same time. In this context, the World Health Organization recommends including the following criterias for assessment of life quality: usage of the space, protection of historical, cultural and natural values, accessibility to services, planning, building design, urban design [12].…”
Section: Life Quality Descriptionsmentioning
confidence: 99%
“…The excellent performance of fuzzy logic has been tested by many researchers in their models. Oh and Jeong (2002), for example, showed that the fuzzy set approach performed better than a Boolean approach in evaluating the urban residential environment. Fuzzy logic supplies us with a suitable tool to analyze some problems related to land classification.…”
Section: Knowledge-based Intelligent Systemsmentioning
confidence: 99%
“…In recent years, the theory of fuzzy logic has been applied in many studies of urban planning (see, for example, Dragicevic et al, 2001;Heikkila et al, 2003;Oh and Jeong, 2002). For multicriteria decisionmaking, the concept of a membership function is used.…”
Section: Definition Of Membership Functionsmentioning
confidence: 99%